A Descriptive Study to Assess the Knowledge and Attitude Towards Care of Dying Patients among Nursing Interns - Saidama Sherif Mujavar; Nayana K; Revathi S Nair; Riya Babu; Gireesh G R (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background of the Study: Death is inevitable for all living beings. Nurses play a vital role in care of dyingpatients and their family. Regardless whether the death occurs, in the community or hospital nurses spendslargest proportion of time during the care of dying patients. The nurses concern and support are valued bypatients as well as the relativesAim: To examine the nursing intern’s knowledge and attitude towards care of dying patient.Method and Materials: A quantitative research approach with non-experimental descriptive study wasadopted in this study. The stratified random sampling technique was used to select the subject for the study.Data collected from 100 subjects were analyzed by descriptive and inferential statistics using SPSS version22.Result: Among the selected subjects 83% had average knowledge, 69% had neutral attitude towards careof dying patients.Conclusion: In the present study by assessing the level of knowledge and attitude of Nursing interns towardscare of dying patients, it was found that 83% of Nursing interns had average knowledge and 69% of Nursinginterns had neutral attitude towards care of dying patients. This chapter enlightens the need of the researchstudy. The research reveals that there is no association between level of knowledge, level of attitude withselected demographic variables and there is no significant relationship between level of knowledge andattitude of Nursing interns towards care of dying patients.